2012
DOI: 10.1109/tcsvt.2011.2168269
|View full text |Cite
|
Sign up to set email alerts
|

SSIM-Motivated Rate-Distortion Optimization for Video Coding

Abstract: Abstract-We propose a rate-distortion optimization (RDO) scheme based on the structural similarity (SSIM) index, which was found to be a better indicator of perceived image quality than mean-squared error, but has not been fully exploited in the context of image and video coding. At the frame level, an adaptive Lagrange multiplier selection method is proposed based on a novel reduced-reference statistical SSIM estimation algorithm and a rate model that combines the side information with the entropy of the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(98 citation statements)
references
References 41 publications
0
98
0
Order By: Relevance
“…This largely restricts its applications in designing image processing algorithms such as image compression and restoration. Recently, some works [36][37][38] have been reported to adopt SSIM for image/video perceptual compression. However, these methods are not "one-pass" and they have high complexity.…”
Section: G Discussionmentioning
confidence: 99%
“…This largely restricts its applications in designing image processing algorithms such as image compression and restoration. Recently, some works [36][37][38] have been reported to adopt SSIM for image/video perceptual compression. However, these methods are not "one-pass" and they have high complexity.…”
Section: G Discussionmentioning
confidence: 99%
“…Most of the existing compression schemes still adopt MSE or PSNR during RDO, which does not well correspond to visual quality. Optimizing compression for visual quality is a promising direction to further improve compression ratio, such as using SSIM to replace PSNR [29]. More recently, a perceptual screen content coding scheme is developed based on the newly proposed quality assessment measure [28].…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, it was found that, despite several uses of SSIM [9][10][11], in most cases MSE is employed for optimization in coding. "Why the state-of-theart FR IQA models cannot be applied to compression?"…”
Section: Proposed Quality Metricmentioning
confidence: 99%
“…the mean opinion score (MOS). Subjective quality scores are quite valuable, because on the one hand they can be used to justify the performance of objective IQA algorithms (e.g., LIVE [1], TID2008 [2], CSIQ [3], IVC [4], Toyama [5] and TID2013 [6]), and on the other hand, they are able to instruct denoising [7], restoration [8], coding [9][10][11], and compare tone-mapped operators [12][13][14]. But subjective methods easily suffer the drawbacks of being laborious, costly and time-consuming, and thus cannot be adapted to real-time applications.…”
Section: Introductionmentioning
confidence: 99%